Propuesta para la determinación del radio de incidencia del 131I a través de una metodología de muestreo en la cuenca media del río Bogotá (2018)
The present work of a preliminary view of radioactive contamination caused by I131 in the Bogotá River, the use of a radionuclide in nuclear medicine for the treatment and diagnosis of thyroid cancer, however, the source that causes the presence of this Radionuclide in the river is still a mystery, it is believed that it is the cause of the patients treated on an outpatient basis and of the discharges of the hospitals that manage this branch of medicine.